Beninese vaccination clinic - Sun, Linda (Canadian Medical Education Journal, 2017)
This photo was taken in the village of Ladji, which is on the outskirts of Cotonou, the capital of Benin. At the time, I was a second year medical student volunteering at a local medical clinic. On every Wednesday morning, many Beninese babies, like this one, cry out of discomfort while receiving their monthly vaccinations. The photo shows a local clinic nurse administering the vaccination.